The Knowledge of God’s Will: On Spinoza’s Construction of the Prophets’ Theology - Bolin PENG , (Journal of Research for Christianity in China (JRCC), 2024)
Theological-Political Treatise is a pioneering work of biblical criticism. On the basis of discussing the history and literature of Old Testament, Spinoza gives high comments to the Prophets’ theology, and thinks that the prophets agree with himself. With the aim of seperating theology from philosophy, God’s will from God’s essence, Spinoza skillfully constructs the system of the Prophets’ theology by biblical philology, and read into them his own philosophy by covertly intercepting or distorting the texts. Avoiding the propblem of God’s essence, around the concept of God’s will, Spinoza thinks that the classical prophets are the people who truely understand God’s will and are the hope of true theology, true religion, as well as future universal religion. Because the prophets turely know that God’s will is virtue but not law, they know God’s will by visual and audiological power of natural imagination, they have indicate that the true ways to obey God’s will are practicing justice and loving-kindness. So the prophets’ knowledges of God’s will are true and integral, and have absolute authority in religious classical texts, theologies and livings.
Keywords: Theological-Political Treatise, Spinoza, the Prophets, theology, God’s will